Phytochemical Screening and Antioxidant Capacity of Banana Peel Ethanol Extract of Ketip (Musa paradisiaca Forma Typiaca) on Sperm Concentration and Motility of Mice (Mus musculus) - Syamsul Bahri; Dadi Setiadi; Tri Ayu Lestari; Muhamad Yazid Mizanul Ilmi (Green Engineering Society, 2026)
This study examines the effect of ethanol extract of banana peel ketip (Musa paradisiaca Forma Typiaca) on sperm concentration and motility of mice (Mus musculus) following cigarette smoke exposure. This study aims to determine the phytochemical content and antioxidant capacity of the extract after cigarette smoke exposure. This study began with extracting chemical compounds from the sample, followed by phytochemical screening to determine their content. The antioxidant capacity of the extract was examined using the DPPH method with a UV-Vis spectrophotometer and an in vivo test using adult male mice. Sperm concentration and motility data were analyzed by one-way ANOVA and Tukey’s HSD test. The phytochemical screening results showed that the ketip banana peel ethanol extract contains terpenoids, alkaloids, flavonoids, tannins, and saponins. The DPPH test results showed that the IC50 value of the extract was 554.84 ppm. Statistical analysis of the in vivo data showed that the ethanol extract of ketip banana peel significantly increases sperm concentration (p value = 0.005486; F value 4.197422; F critical= 2.510158) and motility (P value= 0.0000; F value =41.59092; F critical= 2.510158) following cigarette smoke exposure. Tukey’s HSD analysis of sperm concentration (HSD score = 2.271) showed that the 5000 ppm extract significantly increases sperm concentration without cigarette smoke exposure and sperm concentration after 5 minutes of cigarette smoke exposure. Nevertheless, this treatment failed in restoring sperm concentration following 30 minutes of cigarette smoke exposure. This indicates that longer duration of cigarette smoke exposure causes severe damage to sperm production (spermatogenesis) that is difficult to restore, even with high-dose treatment. Tukey’s HSD analysis of sperm motility (HSD score = 0.207) showed that treatment with the ethanol extract of Ketip banana peel alone insignificantly increases sperm motility. The decrease in sperm motility after cigarette smoke exposure was significantly restored with high doses of the peel extract. These findings suggest that the sperm maturation stage, where the sperm motility is determined, was protected by antioxidant substances contained in the ethanol extract of Ketip banana peel.